There's something rotten in the state of Texas: Genre, adaptation and The Texas Vibrator Massacre. (1st November 2013) - Watson, Thomas
The main focus of this article is to critically assess the recent hardcore porn film The Texas Vibrator Massacre. Following the decision of the British Board of Film Classification (BBFC) to ban the film in August 2008, this article explores the contexts of such regulatory control in response to what has proven to be a problematic conflation of hardcore porn and horror. Although the film is coded as a sex work, its callous tone and representations of violence have meant that the film complicates what is, on the surface, a pornographic parody film. Using the rejection of the film as a starting point, the article explores the now conventional porn parody sub-genre and how Rob Rotten positions himself in relation to this type of pornography. Moving beyond issues of parody and into the controversial representation of sexual violence, I position The Texas Vibrator Massacre as an example of both hardcore porn and graphic horror that problematizes the critical assessment of these respective genres. In discussing the film through the prism of censorship and the practicalities of classification, I argue how this framework of regulation can be used to outline the wider implications of conflating horror and hard-core pornography.